Local Wisdom-Based Competitive Advantage Strategy in Small and Medium Businesses - Sandy Gunawan (Universitas Prasetiya Mulya, 2026)
Small and medium enterprises (SMEs) play a significant role in the Indonesian economy. However, SMEs face several obstacles in developing their businesses and creating competitive advantages. As a business unit in the developing stages, SMEs are greatly influenced by the values adopted by the owner. Developing competitiveness requires SMEs to consider aspects of wisdom and values ​​in the area where the SMEs are located. SME development through the integration of local values ​​with business strategies will help better illuminate how these values ​​influence business sustainability and competitiveness. The research attempts to determine the effect of traditional values ​​on business strategies conducted by SMEs and its influence on competitiveness. The research focuses on SMEs in Badung Regency, Bali. Balinese people are known to uphold their traditions and customs in their lives. This study shows that local wisdom and values ​​can serve as guidelines as a strategy to increase SMEs’ competitiveness of SMEs.